Constitutional review and the achievement of higher performance in democratized local government system of Delta and Edo State - Afonughe Irikefe Omamuyovwi; Mukoro Akpomuvire; G C Sokoh (Journal of Social Studies (JSS), 2023)
This paper x-rayed the importance of constitutional review as the instrument or tool to achieve effectiveness; in the local government systems of Delta and Edo States. It is rather good to mention that every system whether as a body or an institution of governance needs good legislations as a constitutional framework to enable its performance or pragmatism because without it there will not be direction of focus as well as accountability, hence the constitution is the oxygen of the state as well as government in the forms of arms, tiers and agencies. Local government performance in Nigeria, especially Delta and Edo States as the focal points is at dismal state in terms of performance, rural communities are a continuous shadow of themselves and this is as a consequence to the faulty constitutional arrangements that has gone a long way to pervasively strangulated this third tier of government to the extent that their essence of creation is far apart from the reality on ground. Thus, this constitutional deformity has spiral into various problems such as oppression from the state agencies, general indiscipline among the cadre of workers in the local government system, inadequacy of skilled workers among others. The study therefore, arrived at some recommendations such as: The need for urgent constitutional review to reform the laws that dictate the whims and caprices of the local government system, local government autonomy entailing financial and administration should be ensured, the state joint local government account should be entirely abolished. The study concludes that the legislature as an organ of government should be sincere to enforce the political will of a good constitutional reform for an effective local government performance.